Diabetes Epidemiology Among Adults in Port-au-Prince, Haiti: A Cross-Sectional Study - Sufra, Rodney; Lookens Pierre, Jean; Dade, Eliezer; Rouzier, Vanessa; Apollon, Alexandra; St Preux, Stephano; Préval, Fabiola; Inddy, Joseph; Metz, Miranda; Tymejczyk, Olga; Nash, Denis; Malebranche, Rodolphe; et al. (Frontiers in Endocrinology, 2022)
Introduction Diabetes mellitus is a chronic noncommunicable disease associated with death and major disability, with increasing prevalence in low- and middle-income countries. There is limited population-based data about diabetes in Haiti. The objective of this study was to assess the prevalence of diabetes and associated factors among adults in Port-au-Prince, Haiti using a population-based cohort. Methods This study analyzes cross-sectional enrollment data from the population-based Haiti Cardiovascular Disease Cohort Study, conducted using multistage sampling with GPS waypoints in census blocks in the metropolitan area of Port-au-Prince, Haiti. A total of 3,005 adults ≥18 years old were enrolled from March 2019 to August 2021. We collected socio-demographic data, health-related behaviors, and clinical data using standardized questionnaires. Diabetes was defined as any of the following criteria: enrollment fasting glucose value ≥ 126 mg/dL or non-fasting glucose ≥ 200 mg/dL, patient self-report of taking diabetes medications, or study physician diagnosis of diabetes based on clinical evaluation. Results Among 2985 (99.3%) with complete diabetes data, median age was 40 years, 58.1% were female, and 17.2% were obese. The prevalence of diabetes was 5.4% crude, and 5.2% age standardized. In unadjusted analysis, older age, higher BMI, low physical activity, low education were associated with a higher odds of diabetes. After multivariable logistic regression, older age (60+ vs 18-29, OR 17.7, 95% CI 6.6 to 47.9) and higher BMI (obese vs normal/underweight, OR 2.7, 95% CI 1.7 to 4.4) remained statistically significantly associated with higher odds of diabetes. Conclusion The prevalence of diabetes was relatively low among adults in Port-au-Prince, but much higher among certain groups (participants who were older and obese). The Haitian health system should be strengthened to prevent, diagnose, and treat diabetes among high-risk groups.